Cutaneous horn arising from a basal cell carcinoma of forehead: a case report - Sivaramakrishnan, S.; Thomas, Jayakar (International Journal of Research in Dermatology, 2019)
The term cutaneous horn or “cornu cutaneum” is used to describe a well circumscribed usually conical hyperkeratotic mass arising from another cutaneous lesion. Several lesions have been reported to occur at the base of the keratin mass. Here we report a rare case of cutaneous horn arising from a basal cell carcinoma (BCC) over the forehead of a 52 year old female patient.